2019
DOI: 10.3390/en12132634
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Reuse of Industrial CO2 Emissions Using a Microalgae Photobioreactor: Waste Heat Utilization Assessment

Abstract: Microalgae are a potential means of recycling CO2 from industrial point sources. With this in mind, a novel photobioreactor (PBR) was designed and deployed at a coal-fired power plant. To ascertain the feasibility of using waste heat from the power plant to heat algae cultures during cold periods, two heat transfer models were constructed to quantify PBR cooling times. The first, which was based on tabulated data, material properties and the physical orientation of the PBR tubes, yielded a range of heat transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this study, it was established that the preculture was performed in a tubular photobioreactor, achieving a final biomass concentration of 1.5 g/L [65], which is then mixed with the culture medium and fed to the raceway pond. It has been reported that the cultivation of biomass in photobioreactors is more efficient in biomass production, but the energy consumption is higher in these systems [66][67][68]. In this case, the preculture consumes 44% of the total energy consumption for the cultivation of biomass, while the rest is associated with the raceway pond (56%).…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…In this study, it was established that the preculture was performed in a tubular photobioreactor, achieving a final biomass concentration of 1.5 g/L [65], which is then mixed with the culture medium and fed to the raceway pond. It has been reported that the cultivation of biomass in photobioreactors is more efficient in biomass production, but the energy consumption is higher in these systems [66][67][68]. In this case, the preculture consumes 44% of the total energy consumption for the cultivation of biomass, while the rest is associated with the raceway pond (56%).…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…As part of their research, microalgae biofuel scientists are focusing their attention on various indicators related to light distribution, such as colour, photosynthetically active PAR irradiance, and the ratio between light and dark periods. Findings from studies on the influence of factors on microalgae growth are used to develop optimal culture strategies under controlled conditions and to design modern photobioreactors [42,46,47]. Thus, different photobioreactor solutions can contribute to increased biomass productivity and optimal energy use for the production of valuable bioproducts.…”
Section: Introductionmentioning
confidence: 99%
“…As photosynthetic organisms consume carbon dioxide in the process of photosynthesis, algae breeding also presents a desirable side-effect of carbon sequestration [9,10].…”
Section: Introductionmentioning
confidence: 99%